Emoji in social media discourse about working from home. (December 2021) - Zappavigna, Michele; Logi, Lorenzo
Abstract: This paper applies a social semiotic framework for exploring the functions of emoji in digital discourse about working from home (WFH). This is an important and prevalent discourse in the on-going COVID-19 pandemic due to widespread 'lockdowns' aimed at reducing the spread of the virus which have had a profound impact upon how and where people work. The paper focuses in particular on ideational meaning, that is, how experience is construed, exploring how people use language and emoji to express ideational meanings about their daily lives in a large corpus of tweets about WFH. This exploration involves corpus-based discourse analysis focused on how language and emoji coordinate to make meaning, drawing on the concept of intermodal coupling to understand the convergence of meaning across semiotic modes. The paper also considers the role of visual images in this coordination.